Heterorhabditis and Photorhabdus Symbiosis: A Natural Mine of Bioactive Compounds - Parihar, Ripu Daman; Dhiman, Urvashi; Bhushan, Anil; Gupta, Prashant Kumar; Gupta, Prasoon (Frontiers in Microbiology, 2022)
Phylum Nematoda is of great economic importance. It has been a focussed area for various research activities in distinct domains across the globe. Among nematodes, there is a group called Entomopathogenic nematodes which has two families Steinernematidae and Heterorhabditidae that lives in symbiotic association with bacteria of genus Xenorhabdus and Photorhabdus respectively. With the passing years, researchers have isolated wide array of bioactive compounds from these symbiotically associated nematodes. In this article we are encapsulating bioactive compounds isolated from members of family Heterorhabditidae inhabiting Photorhabdus in its gut. Isolated bioactive compounds have shown a wide range of biological activity against deadly pathogens to both plants as well as animals. Some compounds exhibit lethal effects against fungi, bacteria, protozoan, insects, cancerous cell lines, neuroinflammation etc with great potency. The purpose of this appraisal is to outline the importance of nematode and its associated bacteria as this source is not much explored yet by pharmaceutical industry for the commercial production of drugs.